ORIENTALISME DALAM CERPEN ROBOHNYA SURAU KAMI KARYA A.A. NAVIS - Kasimbara, Devi Cintia (Jurnal Lentera merupakan Jurnal Prodi Pendidikan Bahasa Indonesia yang berkala mempublikasikan artikel ilmiah dari hasil penelitian berupa pengajaran dan pendidikan Bahasa Indonesia. Secara khusus, jurnal ini berisi penelitian tentang pengajaran, pen, 2019)
The main discussion of this research is analyzing orientalism practical in Robohnya Surau Kami which narrates about a grandfather who finally commits suicide. It could happen since he is deceited by a liar, Ajo Sidi, who follows colonialism. The existence of East image and West image in Kakek Garin and Ajo Sidi characters leads the researcher to analyze the orientalism practical in Robohnya Surau Kami. In order to find how A.A. Navis describes characters, the orientalism theory by Edward W. Said is used by seeing life values that are followed by characters in this short story. The life values in this story are representation from West view toward the East. The result of this research is that the short story which is written by A.A. Navis has represented its characters in East and West view. The character of Kakek Garin is the representation of East who has characters from East world and Ajo Sidi is the representation of West who is seen as having characters from West world. Keywords: A.A. Navis, Robohnya Surau Kami, Orientalism, West and East.